Phenomenology and Hermeneutics in Contemporary Ukrainian Historic-Philosophical Research - Kebuladze, Vakhtang (Sententiae, 2013)
The paper deals with the contemporary Ukrainian historic-philosophical investigations of phenomenology and hermeneutics. Phenomenology and hermeneutics are treated on the one hand as trends in the modern philosophy, on the other hand as methods of historical and philosophical research. The author also shows that phenomenology is considered by contemporary Ukrainian scholars as philosophy of experience.